A contribution to the genus Afronurus Lestage, 1924 in China (Ephemeroptera: Heptageniidae, Ecdyonurinae) - Zhang, Wei; Lei, Zhi-Ming; Li, Wen-Juan; Zhou, Chang-Fa (European Journal of Taxonomy, 2021)
The genus Afronurus has several very common mayfly species in China and they are widely distributed in this country. Some of them are quite similar to each other in both imaginal and nymphal stages. However, these species have not been systematically compared and reviewed so far. In this study, six species are recognized. All nymphs of them share the following characters: gills V–VI with additional arrow-like accessory lobes, branched dentisetae, two rows of bristles and setae on hindtibiae and spotted abdominal terga. The males have divergent penes and clearly expressed titillators. The nymphs of the new species A. drepanophyllus sp. nov. have sickle-like gills I, spotted and striped body color, and males have unique genitalia. The nymphal stages of A. furcatus and A. hunanensis, which are associated and described for the first time, have similar body color to A. drepanophyllus sp. nov., but their pale dots on the head capsules and the shape of the hypopharynx are different. Keys to males and nymphs of the six species are provided.